2022
DOI: 10.1039/d2an00475e
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly sensitive optical nanoantenna for bacterial detection

Abstract: Gold nanoparticles (AuNPs) are chemically stable and serve as excellent labels because their characteristic red coloration based on the localized surface plasmon resonance does not fade. However, it is necessary...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Bacterial cultures and all experiments were developed and managed in a Biosafety Level 2 laboratory in accordance with the appropriate safety regulations (WHO Laboratory Biosafety Manual). 6,7 The bacterial strain was cultured in an agar growth medium (E-MC35, Eiken Chemical, Japan) at 310 K for 18 h. A single colony was selected, placed in a liquid growth medium (5.0 mL), and incubated at 310 K for 6 h. The precipitate was dispersed in sterile ultrapure water and the E. coli K12 suspension concentration was adjusted to 3.6 © 10 11 CFU mL ¹1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial cultures and all experiments were developed and managed in a Biosafety Level 2 laboratory in accordance with the appropriate safety regulations (WHO Laboratory Biosafety Manual). 6,7 The bacterial strain was cultured in an agar growth medium (E-MC35, Eiken Chemical, Japan) at 310 K for 18 h. A single colony was selected, placed in a liquid growth medium (5.0 mL), and incubated at 310 K for 6 h. The precipitate was dispersed in sterile ultrapure water and the E. coli K12 suspension concentration was adjusted to 3.6 © 10 11 CFU mL ¹1 .…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In recent years, many studies have reported on the development of biosensors using novel materials and technologies. For highly sensitive and rapid detection of pathogenic bacteria, biosensors based on physical or chemical signals, such as light scattering, [6][7][8][9] fluorescence, 10,11 electrochemistry, [12][13][14][15] and piezoelectricity, 16 have been developed. In particular, electrochemical biosensors are particularly useful in fields where on-site testing is required because of their high sensitivity, rapid measurement, and ease of device miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…Localized surface plasmon resonance (LSPR) phenomenon will occur when the frequency of the incident light is consistent with the natural frequency oscillation of the electrons on the metallic nanoantenna surface, resulting in the enormous electric field [3][4][5]. Nanoantenna structures supporting LSPR offer a way to break the optical diffraction limit by concentrating light into subwavelengths [6][7][8][9]. The distribution of the electric field depends on the configuration of plasmonic nanoantenna, which typically exhibits strong enhancement and localization on the surface of the antenna, especially at the smaller tips and gaps of dimers or polymers [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to bulk metals, metal nanoparticles possess unique properties such as catalytic activity and localized surface plasmons due to specific surface area effects. In addition, using glass or a polymer to protect the metal nanoparticles facilitates their stable dispersion and optimizes their exceptional characteristics. Conductive polymers such as polyaniline (PANI), polypyrrole, and PEDOT can be easily synthesized using chemical and electrochemical methods and can be easily hybridized with metal nanoparticles. The hybridization of metal nanoparticles and conductive polymers is expected to endow various functions, such as environmental stability, electrical conductivity, and electrochemical activity. , Previously, we successfully developed organic–inorganic hybrids with a densely assembled structure of gold nanoparticles (AuNPs) in a PANI matrix. This fabrication method exploited the fact that the reduction of aurate by aniline and the oxidation of aniline by aurate occurred in the same reaction field, enabling the production of nanometer-scale hybrids in a single process. We attempted to detect bacteria using the characteristic optical and electrochemical properties of the hybrids. …”
mentioning
confidence: 99%